IMPLEMENTASI MODEL PEMBELAJARAN BERKARAKTERISTIK SAINTIFIK PADA MATA KULIAH PERENCANAAN PEMBELAJARAN KIMIA - FNU Hartono (Chemistry Education Study Program Sriwijaya University, 2020)
This descriptive qualitative research aims to describe the implementation of scientific learning models (MPBS) in the Chemistry Learning Plan course for the 5th semester students of Chemistry Education Study Program at the Indralaya Campus FKIP Sriwijaya University 2016/2017 academic year. The research is part of the MPBS Development Research. The research data collection methods are documentation, observation, questionnaire, and tests. Data were analyzed descriptively. The results of the study are as follows. (1) MPBS can be implemented well in Chemistry Learning Planning courses. (2) The five stages of MPBS in learning Chemistry Learning Planning courses are problem confrontation, data collection and verification, data collection and experimentation, explanation, and analysis of the learning implementation process. (3) Student learning outcomes increase increase (gain = 44%). Thus the implementation of MPBS can be carried out optimally and student learning outcomes can be improved by the medium category. Key words: Learning Model, Scientific, Lesson Plan of Learning Chemistry